A New Tymovirus Isolated From Solanum quitoense Characterization and Prevalence in Two Solanaceous Crops in Ecuador - Cornejo-Franco, Juan F (Plant disease, 2019)
Naranjilla (Solanum quitoense Lam.) and tamarillo (S. betaceum Cav.) are two important perennial solanaceous crops grown in Ecuador for the fresh market and juice production. Viruses infecting tamarillo and naranjilla are currently poorly studied, and no clean stock program exists in Ecuador. Here, we report a new virus, provisionally named as naranjilla mild mosaic virus (NarMMV) (genus Tymovirus, family Tymoviridae), isolated from naranjilla grown in an orchard in Pichincha Province, Ecuador. The complete genome of the virus consists of 6,348 nucleotides and encodes three open reading frames typical for members of the genus Tymovirus. Phylogenetically, Chiltepin yellow mosaic virus, Eggplant mosaic virus, and the recently characterized naranjilla chlorotic mosaic virus (NarCMV) were found to be the closest relatives of NarMMV. Unlike NarCMV, the new virus induced mild mosaic in naranjilla and more severe symptoms in tamarillo. Similar to NarCMV, NarMMV was unable to systemically infect potato. Virus surveys found NarMMV prevalent in naranjilla production areas of two provinces of Ecuador, especially where hybrid cultivars of naranjilla were cultivated. NarMMV was also found in field-grown tamarillo. The new virus cross-reacted with antibodies developed against NarCMV. Hence, this antibody will be useful for its field diagnosis using enzyme-linked immunosorbent assay or immunocapture reverse transcription polymerase chain reaction in future virus-free certification programs